Orthography: Error Analysis of Speech Texts of Arabic Language Education Students - Oca Oktavia; Yulia Rahmah; Aulia Mustika Ilmiani; Asmaa Hassan Elnwery (PPPBA, 2024)
This study examines orthography errors in Arabic speech texts of fourth semester students of the Arabic Language Education Study Program at IAIN Palangka Raya, where not all students are able to correctly describe the sounds of the language into writing. Orthography is the specification of sounds in a language that is mapped or described from a particular writing, in this case, Arabic. This research uses a descriptive qualitative approach by using primary data sources such as Arabic speech texts and secondary data from relevant literature. The data collection stage includes literature study, interviews, observation, and documentation, while data analysis uses orthographic methods with basic techniques (orthographic sorting technique) and advanced techniques (comparative linking technique). The results show that orthographic errors in Arabic script can be divided into two types: first, single errors which include the addition or subtraction of vowels and consonants, subtraction of consonant punctuation marks, and letter changes. Second, errors with two or more types. The factors underlying these errors include sociolinguistic and psycholinguistic aspects of IAIN Palangka Raya students.